2022
DOI: 10.21037/tlcr-22-273
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell-free DNA and circulating tumor cells as prognostic biomarkers in small cell lung cancer patients

Abstract: Background: Lack of biomarkers for treatment selection and monitoring in small-cell lung cancer (SCLC) patients with the limited therapeutic options, result in poor outcomes. Therefore, new prognostic biomarkers are needed to improve their management. The prognostic value of cell-free DNA (cfDNA) and circulating tumor cells (CTCs) have been less explored in SCLC.Methods: We quantified cfDNA in 46 SCLC patients at different times during first-line of chemotherapy or chemo-immunotherapy. Moreover, CTCs were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Consistent with other studies, ctDNA monitoring has also been shown to identify disease recurrence prior to disease progression seen on imaging or in cases where imaging is equivocal [ 121 , 122 , 127 ]. Similar results were found in other studies, where cfDNA levels were found to be associated with disease outcome, as patients with high levels had a worse prognosis [ 129 ].…”
Section: Developing Non-invasive Diagnosticssupporting
confidence: 91%
“…Consistent with other studies, ctDNA monitoring has also been shown to identify disease recurrence prior to disease progression seen on imaging or in cases where imaging is equivocal [ 121 , 122 , 127 ]. Similar results were found in other studies, where cfDNA levels were found to be associated with disease outcome, as patients with high levels had a worse prognosis [ 129 ].…”
Section: Developing Non-invasive Diagnosticssupporting
confidence: 91%
“…CfDNA levels are influenced by multiple factors such as age, metabolic activity, immune processes and disease, such as cancer (33). In patients with different solid tumour types cfDNA levels are found increased in comparison with healthy people and has been associated with poor prognosis in advanced stages (30,34) and, appart from the contribution of the tumour derived cfDNA in this increment, the neoplasic transformation may have systemic effect on cell turnover or DNA clearance associated with the cfDNA dynamic (30). In the present study we have shown that pre-surgery assessment of cfDNA levels correlates with poor clinical outcome, being a robust and independent prognostic biomarker for EC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Tamminga et al have shown that CTCs occur in one-third of advanced NSCLC patients, and their presence is of high prognostic and predictive value before and after immunotherapy [ 30 ]. In SCLC, that 5-year relative survival rate is extremely low; the use of a much higher cut-off equivalent to 150 CTCs/7.5 mL of whole blood also has clinical utility [ 31 ]. In a phase II multicenter adaptive immunotherapy trial of 457 longitudinal liquid biopsies from 104 patients with Metastatic Renal Cell Carcinoma (mRCC), the change over time of CTC enumeration is of prognostic importance [ 32 ].…”
Section: Clinical Significance Of Ctcs In Immunotherapymentioning
confidence: 99%